Development of an Oil-in-Water Self-Emulsifying Microemulsion for Cutaneous Delivery of Rose Bengal: Investigation of Anti-Melanoma Properties - Farzaneh Forouz; Maryam Dabbaghi; Sarika Namjoshi; Yousuf Mohammed; Michael S. Roberts; Jeffrey E. Grice (MDPI AG, 2020)
The topical delivery route is proposed as an alternative or adjunctive approach to melanoma treatment, since the target site for melanoma treatment-the epidermal basal layer-is potentially accessible by this route. Microemulsion systems are effective delivery vehicles for enhanced, targeted skin delivery. This work investigated the effect of Rose Bengal (RB) and RB-loaded self-emulsifying microemulsions (SEMEs) on growth inhibition of human melanoma and normal skin cell monolayers, the safety of the excipients incorporated in SEMEs on human cell lines, and the in-vitro human skin penetration of RB delivered in SEMEs and control solution. Cellular toxicity was assessed by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, and the growth inhibitory mechanism of RB was investigated by flow cytometry using PI staining. Unloaded SEMEs caused reduced cellular toxicity compared to the surfactant excipient, Labrasol®. RB-loaded SEMEs increased cell growth inhibition compared to the RB aqueous solution. Flow cytometry revealed apoptotic cells after treatment with RB-loaded SEMEs, indicating that apoptosis may be one of the mechanisms of cell death. Preliminary results of multiphoton microscopy with fluorescence lifetime imaging (MPM-FLIM) analysis showed deeper penetration with greater skin concentrations of RB delivered from SEMEs compared to the RB aqueous solution. This study highlights the enhanced skin penetration and antimelanoma effects of RB loaded in a SEME system.